High‐sensitive clinical diagnostic method for PTPRZ1‐MET and the characteristic protein structure contributing to ligand‐independent MET activation. (28th February 2021) - Huang, Ruoyu; Liu, Yanwei; Wang, Kuanyu; Wang, Zheng; Zhang, Chuanbao; Zhang, Wei; Zhao, Zheng; Li, Guanzhang; Huang, Lijie; Chang, Yuanhao; Zeng, Fan; Jiang, Tao; et al.
Abstract: Background: PTPRZ1 ‐ MET ( ZM ) is a critical genetic alteration driving the progression of lower‐grade glioma. Glioma patients harboring ZM could benefit from MET inhibitors. According to the remarkable role of ZM as a driver of glioma progression and indicator of MET inhibitor sensitivity, it is necessary to detect this alteration even when it presents in glioma with relatively fewer copies. Methods: Herein, we proposed that ZM could be detected with a high‐sensitive method of reverse transcriptase PCR with 50 amplification cycles. Via this newly proposed detection method, we depicted the incidence preference of ZM fusion in a cohort of 485 glioma patients. To further explore the oncogenic nature of ZM, we predicated the protein structure alteration of MET kinase brought by its fusion partner. Results: The incidence of ZM fusions was much higher than previous report. ZM fusions exhibited a striking preference in lower‐grade glioma and secondary glioblastoma. By contrast, none of patients with primary glioblastoma was detected harboring ZM fusion. In each of the four variants of ZM, the fusion partner segment of MET contained a remarkable coiled‐coil motif. In glioma cells expressing ZM, MET kinase could be activated in a ligand‐independent manner, which might be contributed by the special coiled‐coil structure brought by the fusion partner. Corresponding to the 3D structural analysis and cell line experiment, the ZM positive clinical specimens showed hyperactivations of MET signaling. Conclusions: ZM fusions are critical drivers of glioma progression and effective target of MET inhibitor. Early detection could be performed with a high‐sensitive method of reverse transcriptase PCR. The hyperactivations of MET signaling driving glioma progression might be contributed by a ligand‐independent activation enabled by the protein structure modification of extracellular domain of MET in ZM fusions. Abstract : Glioma tissue RNA was abstracted after surgery. RT‐PCR of 50 amplification cycles then was performed with the primers designed based on the PTPRZ1 and MET segments that are common to all the four ZM fusion variants. The PCR products of different ZM variants were of different sizes. All the PCR product bands on agarose gel were purified and sequenced via Sanger sequencing. The sequencing reads were aligned to the known ZM fusion sequences. The existence and the variant of ZM fusions then was confirmed and clinically reported.